Migrating humpback whales show no detectable response to whale alarms off Sydney, Australia - Pirotta, Vanessa; Slip, David; Jonsen, Ian D.; Peddemors, Victor M.; Cato, Douglas H.; Ross, Geoffrey; Harcourt, Robert (Endangered Species Research, 2016)
Migratory Group V (Stock E1) humpback whales Megaptera novaeangliae are at risk of entanglement with fishing gear as they migrate north and south along the east coast of Australia. This study investigated the effectiveness of 2 distinct tones for use as an alarm to acoustically alert whales to fishing gear presence and therefore reduce the chance of entanglement. We compared how whales responded in terms of changes of surface behaviour and changes in direction of travel in response to 2 acoustic tones and when there was no alarm. These 2 acoustic tones were a 5 kHz tone (5 s emission interval and 400 ms emission duration, similar to but higher frequency than the signal from a Future Oceans F3™ 3 kHz Whale Pinger®) and a 2-2.1 kHz swept tone (8 s emission interval and 1.5 s emission duration). A total of 108 tracks (focal follows) were collected using a theodolite at Cape Solander, Sydney, Australia, during the whales' 2013 northern migration. Linear mixed effects models were used to determine the effect of the different acoustic tones on whale direction (heading), and behaviour (dive duration and speed). Whales showed no detectable response to either alarm. Whale direction and surfacing behaviour did not differ whether the alarm was 'on' or 'off'. Although the response may have been different if the alarms were attached to fishing gear, the lack of measurable response suggests that the types of tones used are not likely to be effective in alarms intended to reduce entanglement of northward migrating Australian humpback whales.